2021
DOI: 10.3389/fpls.2021.694153
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic Flowering Response of Essential Oil, Grain, and Fiber Hemp (Cannabis sativa L.) Cultivars

Abstract: Cultivation of hemp (Cannabis sativa L.) in tropical and subtropical regions can be challenging if the flowering behavior of a given cultivar is unknown, poorly understood, or not accurately selected for the photoperiod. Identifying cultivars adapted to local environmental conditions is key to optimizing hemp vegetative and flowering performance. We investigated the effects of varying light cycles in regulating extension growth and flowering response of 15 essential oil and 12 fiber/grain hemp cultivars both i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 34 publications
3
32
0
Order By: Relevance
“…On the other hand, it is known that the photoperiod can directly influence the EO content and composition, so that the leaf number, as well as the EO content, gradually increased with an increasing the photoperiod (time), where the shorter days (12 h) lead to a reduction in areal part growth and EO content. Although we did not control or perform experiments to understand the effect of photoperiod on the sage EO, there are reports in which the photoperiod role is emphasized as critical in the final EO content (for example, in Cannabis sativa [42] and Mentha species [43]). A similar variation of the EO percentage, depending on the harvesting time of the day, has been found in Matricaria chamomile [44], Lavandula officinalis [45], Ocimum x citriodorum [39], and Mentha piperita [46].…”
Section: Essential Oil Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is known that the photoperiod can directly influence the EO content and composition, so that the leaf number, as well as the EO content, gradually increased with an increasing the photoperiod (time), where the shorter days (12 h) lead to a reduction in areal part growth and EO content. Although we did not control or perform experiments to understand the effect of photoperiod on the sage EO, there are reports in which the photoperiod role is emphasized as critical in the final EO content (for example, in Cannabis sativa [42] and Mentha species [43]). A similar variation of the EO percentage, depending on the harvesting time of the day, has been found in Matricaria chamomile [44], Lavandula officinalis [45], Ocimum x citriodorum [39], and Mentha piperita [46].…”
Section: Essential Oil Contentmentioning
confidence: 99%
“…However, the combined effect of light, temperature, and relative humidity in a real situation is required to identify the best harvest time for industrial purposes. Factors such as temperature, intensity, the duration of sunlight, and the relative humidity are the main independent variables affecting the composition of EOs in medicinal plants [39][40][41][42][43][44][45][46]. Among the variables, temperature has a substantial effect on plant physiological processes, especially the photosynthetic pathway and the biochemical and phytochemical compounds produced in this process.…”
Section: Constituents Of the Eomentioning
confidence: 99%
“…Under a continuous light regime of 18 or 24 h, hemp plants remain in the vegetative state. Reproductive growth is initiated after a two-week exposure to 12 h of continuous light daily [ 6 , 22 , 24 ]. However, it has been indicated that some varieties can flower even under a prolonged period of light [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…2000a; Zhang et al, 2021) suggest that the light conditions suggested above are close to optimal for rapid induction of flowering in hemp. Seed yield is comparatively low under these conditions but should be sufficient for various breeding and research purposes such as single seed descent lines and crosses.…”
Section: Short-day Treatment Synchronises the Flowering Time Of Diffe...mentioning
confidence: 90%
“…Under optimal light conditions, flowering initiation is assumed to be instantaneous once the plants have entered the photoperiod-induced phase (Lisson et al, 2000a). The optimal day length varies for different hemp cultivars but has been reported to be between 12 h and 14 h for most cultivars (Zhang et al, 2021). In agreement with this, flowering is readily induced at 12 h day length and delayed at 16 h. Ultra-short days do not provide an additional advantage, as flowering time does not decrease further when compared to short-day conditions (Figure 2).…”
Section: Short-day Treatment Synchronises the Flowering Time Of Diffe...mentioning
confidence: 99%